2017
DOI: 10.1108/jcrpp-08-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and nature of sexual harassment and assault against women and girls on public transport: an international review

Abstract: Structured AbstractPurpose: This paper reports on the findings from a study commissioned by the British Transport Police and the Department for Transport for England and Wales concerning sexual offences and harassment on public transport worldwide. Specifically, it aims to explore the prevalence of such behaviours, through a review of existing survey and interview data regarding women and girls' experiences.Design/methodology/approach: A Rapid Evidence Assessment (REA) was used, the function of which is to: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 13 publications
2
54
0
2
Order By: Relevance
“…Globally, almost on a daily basis women are subject to unwanted attention and sexual harassment when riding PT (Gekoski et al, 2017). As such, the focus of most studies on women's use of PT have been on their safety needs (Matthies et al, 2002;Delbosc and Currie, 2012).…”
Section: The Role Of Gender In Public Transport Usementioning
confidence: 99%
“…Globally, almost on a daily basis women are subject to unwanted attention and sexual harassment when riding PT (Gekoski et al, 2017). As such, the focus of most studies on women's use of PT have been on their safety needs (Matthies et al, 2002;Delbosc and Currie, 2012).…”
Section: The Role Of Gender In Public Transport Usementioning
confidence: 99%
“…Eve teasing (street harassment) and sexual harassment have far-reaching consequences, including both short and long-term socio-emotional consequences and limited access to education for victims (Talboys et al, 2017). Participants' stories highlighted harassment experienced on public transportation, which other studies have found to be commonplace (Dhillon & Bakaya, 2014;Gekoski, Gray, Adler, & Horvath, 2017;Leach & Sitaram, 2007;Tripathi, Borrion, & Belur, 2017). Given the widespread familial and social prohibitions limiting young women's movement, harassment in public and on public transportation remains a significant barrier to young women's education and employment opportunities, as is seen elsewhere in developing countries (Porter et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(c.f. Mazumder and Pokharel 2019;Gekoski et al 2017;Ceccato and Paz 2017;Natarajan et al 2017;Tripathi et al 2017;Chui and Ong 2008). A number of studies have also located the solutions to VAW on public transport in situational measures (c.f.…”
Section: Situational Factors That Facilitate Crimementioning
confidence: 99%